Mabel Thorp Boardman papers - Boardman, Mabel Thorp, 1860-1946.
Correspondence, letterbooks, diaries, drafts, genealogical material, newspaper clippings, printed material, and other papers relating chiefly to Boardman's career in the American National Red Cross, known in its early years as the American Association of the Red Cross, and as a commissioner of the District of Columbia and to her personal life. Documents domestic and foreign policy issues of presidential administrations from William McKinley to Franklin D. Roosevelt. Correspondents include William Howard Taft.
Official of the American National Red Cross.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Taft, William H. -- 1857-1930 -- Correspondence; District of Columbia. -- Commissioner; American Association of the Red Cross; American National Red Cross; United States -- Foreign relations -- 20th century; United States -- Politics and government -- 20th century; Administrators; Businesswomen